ESSENTIAL TRACE ELEMENTS AND ARSENIC IN THERMAL SPRINGS, AFGHANISTAN - Ali Jawadi, Hussain; Malistani, Hasan Ali; Anvar Moheghy, Mohammad; Sagin, Jay (Water, 2021)
Thermal springs are natural hydrogeological features which are highly affected by local volcanism or tectonic activity. Thermal springs are the best source of hydrothermal energy to heat houses and aid in the recovery of skin diseases. However, they consist of some heavy and trace metals such as arsenic, lead, zinc, copper, iron, and so forth. Somehow, the thermal springs of central Bamyan have become contaminated with some essential trace elements. Thus, this study was conducted to assess and determine the number of these trace elements in the thermal springs. To achieve these objectives, a preliminary survey, water sampling, and in situ measurements of physicochemical parameters were conducted in research areas...
Keywords: thermal spring; trace element; arsenic; Bamyan; central Afghanistan; contamination